SISTEM PENERIMAAN PEGAWAI SALES KPR PADA BANK MENGGUNAKAN METODE MULTI-OBJECTIVE OPTIMIZATION ON THE BASIS OF RATIO ANALYSIS - Andreyan Rizky Baskara; Yuslena Sari; Muhammad Adetya Ashari (Lambung Mangkurat University, 2021)
The recruitment of new employees, especially for housing loan sales employees (KPR) is often carried out by banks because the performance evaluation of KPR sales employees is carried out regularly. The large number of prospective employees and the variety of criteria determined for selecting new employees lead to a lengthy decision-making process. Decision Support System (DSS) is basically a comprehensive computer system that can help make decisions and solve problems. The Multi Objective Optimization method on The Basis of Ratio Analysis (MOORA) as a decision-making method is used to build a decision support system. The decision support system is implemented as a web-based application using ATOM software which is integrated with the MySQL database. The Black Box testing method is used to test the system. The results showed that the MOORA method is very suitable to be applied in the decision making of KPR sales employee recruitmentKeywords: Decision Support System, KPR Sales Employee, MOORA Perekrutan pegawai baru khususnya untuk pegawai Sales Kredit Pemilikan Rumah (KPR) sering dilakukan oleh bank karena evaluasi kinerja pegawai sales KPR dilakukan secara berkala. Banyaknya calon pegawai dan beragamnya kriteria-kriteria yang ditentukan untuk menseleksi pegawai baru menyebabkan lamanya proses pengambilan keputusan. Sistem Pendukung Keputusan (SPK) pada dasarnya adalah sistem komputer komprehensif yang dapat membantu membuat keputusan dan menyelesaikan masalah. Metode Multi Objective Optimization on The Basis of Ratio Analysis (MOORA) sebagai salah satu metode pengambilan keputusan digunakan untuk membangun sistem pendukung keputusan. Sistem pendukung keputusan diimplementasikan sebagai aplikasi berbasis web menggunakan perangkat lunak ATOM yang terintegrasi dengan database MySQL. Metode pengujian Black Box digunakan untuk menguji sistem. Hasil penelitian menunjukkan bahwa metode MOORA sangat cocok diterapkan dalam pengambilan keputusan perekrutan pegawai sales KPRKata kunci: MOORA, Pegawai Sales KPR , Sistem Penunjang Keputusan